2016
DOI: 10.1063/1.4939614
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of valence-band offset at native oxide/BaSi2 interfaces by hard x-ray photoelectron spectroscopy

Abstract: Undoped n-type BaSi 2 films were grown on Si(111) by molecular beam epitaxy, and the valence band (VB) offset at the interface between the BaSi 2 and its native oxide was measured by hard x-ray photoelectron spectroscopy (HAXPES) at room temperature. HAXPES enabled us to investigate the electronic states of the buried BaSi 2 layer non-destructively thanks to its large analysis depth. We performed the depth-analysis by varying the take-off angle (TOA) of photoelectrons as 15 , 30 , and 90 with respect to the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…17(c'), the peak intensities of the oxides became stronger for the native-oxide/BaSi2 sample as TOA decreased; the peak located around 151 eV almost disappeared at TOA = 15°. Considering the Si 2s corelevel spectra as well as the Ba 3d5/2 core-level spectra, it is therefore reasonable to assume that a-Si suppresses surface oxidation by capping the surface with a-Si [82,83]. samples [84].…”
Section: Surface Passivationmentioning
confidence: 99%
“…17(c'), the peak intensities of the oxides became stronger for the native-oxide/BaSi2 sample as TOA decreased; the peak located around 151 eV almost disappeared at TOA = 15°. Considering the Si 2s corelevel spectra as well as the Ba 3d5/2 core-level spectra, it is therefore reasonable to assume that a-Si suppresses surface oxidation by capping the surface with a-Si [82,83]. samples [84].…”
Section: Surface Passivationmentioning
confidence: 99%
“…For the a-Si/n-BaSi 2 interface, we found from hard X-ray photoelectron spectroscopy (HAXPES) that the barrier height of the a-Si for the minority-carriers, holes, in the n-BaSi 2 is À0.2 eV, 15 meaning that the transport of holes across the interface is not blocked, whereas this value is approximately 3.9 eV at the native oxide/n-BaSi 2 interface. 16 It was also found that the oxidation of BaSi 2 is suppressed significantly by the a-Si capping layer. The alignment of the valence-band maximums of BaSi 2 (E BaSi 2 V ), its native oxide (E oxide V ), and a-Si (E a-Si V ) is schematically shown in Fig.…”
mentioning
confidence: 98%
“…25 We next investigated its effect on , and a-Si (E aÀSi V ). 15,16 Sample structures used for HAXPES measurements are schematically shown. 0003-6951/2016/109(7)/072103/4/$30.00…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 However, the barrier height of the native oxide/undoped n-BaSi 2 interface for the minority-carriers (holes) in n-BaSi 2 is 3.9 eV. 36 Therefore, the transport of holes generated under solar radiation is blocked at the interface, which results in a limited conversion efficiency of g % 0.1% for a solar cell with the native oxide/n-BaSi 2 interface. 24 For this reason, a-Si was selected as a capping layer in this work.…”
mentioning
confidence: 99%